2016
DOI: 10.1155/2016/1427849
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsy of Hepatocellular Carcinoma: Circulating Tumor-Derived Biomarkers

Abstract: Hepatocellular carcinoma (HCC) is the second leading cause of cancer-related death worldwide due to latent liver disease, late diagnosis, and nonresponse to systemic treatments. Till now, surgical and/or biopsy specimens are still generally used as a gold standard by the clinicians for clinical decision-making. However, apart from their invasive characteristics, tumor biopsy only mirrors a single spot of the tumor, failing to reflect current cancer dynamics and progression. Therefore, it is imperative to devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 98 publications
(91 reference statements)
1
56
0
1
Order By: Relevance
“…. Numerous studies have shown the potential utility of circulating cancer byproducts detection from which we could extract molecular information about primary tumors [51][52][53][54] . The liquid biopsy could be conducted in repeated samples providing accessible, accurate and dynamic information to evaluate the tumor status.…”
Section: Serpinb3mentioning
confidence: 99%
See 2 more Smart Citations
“…. Numerous studies have shown the potential utility of circulating cancer byproducts detection from which we could extract molecular information about primary tumors [51][52][53][54] . The liquid biopsy could be conducted in repeated samples providing accessible, accurate and dynamic information to evaluate the tumor status.…”
Section: Serpinb3mentioning
confidence: 99%
“…The liquid biopsy could be conducted in repeated samples providing accessible, accurate and dynamic information to evaluate the tumor status. These novel biomarkers are thought to have great potential and could provide individualized decision-making during HCC treatment, including the follow-up period; risk assessment, early cancer detection, treatment response or even prognostic outcome [53][54][55][56] .…”
Section: Serpinb3mentioning
confidence: 99%
See 1 more Smart Citation
“…Future criteria will probably include 'liquid biopsies' (23). This emerging concept is based on the ability to detect specific tumor DNA or cancer cells RNA (exosome) in mainstream blood (and other body fluids) (24).…”
Section: Hcc Biological Behaviormentioning
confidence: 99%
“…10,11 We hypothesize that increasing lesion size is associated with a change in biology or aggressiveness, and this has indeed been recently demonstrated. 12 However, other possible contributors to HCC recurrence after OLTx include immune suppression with increased tumor growth, 13,14 circulating tumor cells, [15][16][17][18] enhanced carcinogenesis in the presence of recurrent hepatitis, and patients living longer after transplant, thus having more time for preexisting micrometastases to grow.…”
Section: Why Do Recurrences Occur?mentioning
confidence: 99%